2007
DOI: 10.4049/jimmunol.179.1.266
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Activator of NF-κB Ligand Inhibition Suppresses Bone Resorption and Hypercalcemia but Does Not Affect Host Immune Responses to Influenza Infection

Abstract: Receptor activator of NF-κB (RANK) and its ligand (RANKL) are essential for osteoclast formation, function, and survival. Osteoprotegerin (OPG) inhibits RANK signaling by sequestering RANKL. This study evaluated the antiosteoclast and immunoregulatory effects of mouse rRANK-Fc, which, similar to OPG, can bind RANKL. The effect of RANKL inhibition by RANK-Fc on osteoclast function was determined by inhibition of vitamin D3 (1,25(OH)2D3)-induced hypercalcemia. Mice were injected with a single dose of 0, 10, 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 33 publications
0
30
1
Order By: Relevance
“…Recent studies have shown that administration of OPG or sRANK prevents bone metastasis by cancer cells in vivo (21)(22)(23). These findings suggest that the RANKL/RANK system contributes to bone metastasis by cancer cells.…”
Section: Rankl/rank Signaling Is Involved In Oral Scc Cell-induced Osmentioning
confidence: 72%
See 2 more Smart Citations
“…Recent studies have shown that administration of OPG or sRANK prevents bone metastasis by cancer cells in vivo (21)(22)(23). These findings suggest that the RANKL/RANK system contributes to bone metastasis by cancer cells.…”
Section: Rankl/rank Signaling Is Involved In Oral Scc Cell-induced Osmentioning
confidence: 72%
“…In support of this notion, recent studies in rodent models of breast and prostate cancer have established that inhibition of RANKL/RANK signal decreases bone lesion development and tumor growth in bone (21-23). Alternatively, it has been reported that functional RANK is expressed on some bone-associated tumor cells (21)(22)(23)54). Indeed, the migration of RANK-positive tumor cells is induced by RANKL stimulation.…”
Section: The Role Of Rankl/rank Signaling On Bone Invasion By Oral Sccsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delivery of RANK-Fc as a recombinant protein has shown promising results as a potential therapy through experiments in animal models, in that RANK-Fc limits hypercalcemia and osteolysis induced by myeloma or prostate cancer and reduces bone tumor establishment in these models (15,16,29,36). Moreover, a recent study reported that RANK-Fc inhibition of RANKL has an antiosteoclast activity at doses that have no detectable immunoregulatory activity (37). Even if long-lasting expression of RANK-Fc could be provided at bone-protective levels using a retrovirus-mediated gene transfer approach by the use of genetically modified mesenchymal stem cells (17), the toxicity associated with the use of such viral vectors is extremely complex.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment regimen for RANK-Fc was based on the dose and schedule which optimally inhibits bone resorption in vivo. 32 Twenty-four hours after the first dose of rhApo2L/TRAIL (day 10), a 68% reduction in hind limb tumor burden (as measured by BLI) compared with PBS-treated animals was observed (p < 0.0001; Table 1). Upon cessation of treatment with rhApo2L/TRAIL, skeletal tumors continued to progress (Fig.…”
Section: Mda-mb-231-bb-luc Tumor Cells Are Sensitive To Rhapo2l/ Traimentioning
confidence: 99%